Curious George Takes a Train - Rey, H. A. 1898- (Hans Augusto); Rey, Margret; Weston, Martha (Boston : Houghton Mifflin, 2002)
While waiting for the man with the yellow hat to buy train tickets, Curious George causes trouble by mixing up numbers on the schedule, but he makes up for it when a little boy's toy rolls toward the tracks.
Keywords: Monkeys -- Fiction; Railroad stations -- Fiction